The Francophone bande dessinée - Forsdick, Charles; Grove, Laurence; McQuillan, Libbie (Faux titre ;, 2005)
"Known as France's Ninth Art, the bande dessinee has a status far surpassing that of the equivalent English-language comic strip. This publication, one of the first predominantly in English on the subject, provides a thorough introduction to questions of BD history, context and bibliography. This book supplies an introduction to the BD that will be of use to students and researchers at all levels. In addition, the format of the individual case studies provides in-depth analysis allowing the reader to grasp specific examples in terms both of their place vis-a-vis the evolution of the BD and, more generally, of the wider role they play within French and Francophone cultural studies."--Jacket